Occupational noise exposure and cardiovascular disease in male workers - Lie T. Merijanti (Universa Medicina, 2013)
Noise is a common occupational hazard worldwide. The impact of noise on human health is emerging as an important public health issue. The most well-known effect of high noise levels at work (>85 dBA) is hearing loss that is significantly associated with the period of exposure.(1) In addition, noise exposure can cause non-auditory effects, such as sleep disturbance, annoyance, psychological stress, and cardiovascular disease (CVD). In a study among Korean blue collar workers, Won et al. found that the prevalence of CVD risk was 32 cases per 100 workers.(2)However, the relationship between occupational noise and cardiovascular disease remains unsettled.(3)